Studies on the Feeding Habits of Lutzomyia (Lutzomyia) longipalpis (Lutz & Neiva, 1912) (Diptera: Psychodidae: Phlebotominae) Populations from Endemic Areas of American Visceral Leishmaniasis in Northeastern Brazil - Margarete Martins dos Santos Afonso; Rosemere Duarte; José Carlos Miranda; Lindenbergh Caranha; Elizabeth Ferreira Rangel (Journal of Tropical Medicine)
The aim of this study was to identify potential blood feeding sources of L. (L.) longipalpis specimens from populations in Northeastern Brazil, endemic areas of American Visceral Leishmaniasis (AVL) and its correlation with the transmission of L. (L.) i. chagasi. The ELISA technique was applied using bird, dog, goat, opossum, equine, feline, human, sheep, and rodent antisera to analyze 609 females, resulting in an overall positivity of 60%. In all municipalities, females showed higher positivity for bird followed by dog antiserum and sand fly specimens were also positive for equine, feline, human, sheep, goat, opossum, and rodent antisera. The finding for 17 combinations of two or three types of blood in some females corroborates the opportunistic habit of this sand fly species. The results demonstrating the association between L. (L.) longipalpis and opossum suggest the need for further evaluation of the real role of this synanthropic mammal in the eco-epidemiology of AVL.